First Language Acquisition Analysis Of A One Year Five Month Child “Mateo” - Ni Putu Ayu Niya Loviyani; Ni Nyoman Padmadewi; Luh Gd Rahayu Budiarta; Ahmad Zamzam (UNIB Press, 2022)
First language acquisition has an essential role in children's development. This paper aimed to know the use of language acquisition by a Youtube video. Descriptive qualitative methods have been used to carry out this research. It used five procedures of collecting the data are taking the data from a Youtube video, transcribing the video, classifying, identifying, observing, and analyzing the data. Findings revealed from a child named Mateo that the speech contained phonological, morphological, and syntactical acquisition that showing the development of children in early acquisition. There were 37 words produced with all initial /b/. /d/, /h/, /m/, /n/. /p/. /m/ and /p/ from initial sounds. Then, in syntax acquisition, the researcher found 2 commands. Thus, Mateo’s language acquisition has revealed morphological, phonological, and syntactical acquisition.